THE FORMERS FORMATION: A FIELD TO BE DISCOVERED FROM ITS PROFESSIONAL SECTION - María Cristina Alonso; Silvia Estela Ormaechea (Universidad Nacional del Nordeste, 2015)
Going into - from half of the 90 decade - in the field of formers formation, appeared the neccessity to clarify our epistemological placement to enter upon, that means be conscious of its basis. In thisway the historical, social, cultural and subjective was recovered, as inherent dimensions to complex field in the formers formation. From this decision, three theoretic lines were selected -among others- that put ourselves close to understand the field of formers formation; the relation between epistemology and formation, the sciences in education and the field of formers formation and the problematical of formation from the psychoanalitical point of view, psychosocial and sociological - cultural. To finish with these, we use as an objectiv device of what it is support, the analysis of two singular moments of a group during their way to professional posgraduate formation.